The Role of Auditor Reputation in an Emerging Audit Marketplace: Evidence from Decentralized Finance (DeFi) - Knechel, W. Robert; Maex, Steven A.; Park, Hyun Jong (Management Science, 2026)
We explore the role of auditor reputation in driving the value of smart contract audits (SCAs) within the decentralized finance (DeFi) ecosystem. Given the lack of regulatory oversight and the risk of cybersecurity breaches against the protocols comprising the DeFi ecosystem, a marketplace has emerged for voluntary on-demand assurance to identify vulnerabilities in smart contracts’ coded logic. After documenting that market participants value SCAs and exploring the protocol attributes associated with the demand for smart contract audits, we show that auditor reputation can be established through both advertising (i.e., engagement on Twitter) and the delivery of a high-quality audit, which significantly shape the extent to which an SCA is valued. Additional analyses suggest that the value of an SCA is maximized when both high advertising and high audit quality are present, highlighting the complementary role of these two factors in enhancing auditor reputation. Furthermore, we find that events conceivably damaging the reputation of the auditor (i.e., breaches of protocols recently audited) generate a negative spillover to the auditor’s other recent clients. Overall, our study provides novel insights about the role of auditor reputation in emerging audit markets. This paper was accepted by Suraj Srinivasan, accounting. Supplemental Material: The online appendices and data files are available at https://doi.org/10.1287/mnsc.2023.02245 .